Consumption risk sharing over the business cycle: the role of small firms' access to credit markets - Mathias Hoffmann; Iryna Shcherbakova (Center for Economic Studies and ifo Institute (CESifo), 2009)
Consumption risk sharing among U.S. federal states increases in booms and decreases in recessions. We find that small firms' access to credit markets plays an important role in explaining this stylized fact: business cycle fluctuations in aggregate risk sharing are more pronounced in states in which small firms account for a large share income or employment. In addition, better access of small firms to credit markets in the wake of state-level banking deregulation during the 1980s seems to have loosened the dependence of aggregate risk sharing on the business cycle. Not only do our result support that better access to credit markets may have made it easier for the owners of small firms to smooth income in the face of adverse cash-flows shocks to their business. They suggest a major additional benefit from banking deregulation: access to bank credit has become more reliable and is more easily available when households and firms need it most urgently - in economic downturns.
Keywords: E32; E44; F3; 330; Interstate risk sharing; regional business cycle; proprietary income; small businesses; state banking deregulation; Gesamtwirtschaftlicher Konsum; Konjunktur; Kredit; Klein- und Mittelunternehmen; Bankenpolitik; Teilstaat; Regionaler Konjunkturzyklus; Schätzung; USA